A Case Study of Load Scheduling For Home Energy Management with Integrated Renewable Energy - Tuğba SARIKAYA; Sibel ZORLU PARTAL (International Journal of Engineering and Management Research, 2022)
Smart grids are very comprehensive systems where each sub-unit from generation to consumption should be considered separately. Home energy management systems and demand-side load management applications are also among the most important issues of smart grid systems. In this study, a smart home energy management model was developed in this concept, and energy management solutions were presented through an exemplary model. For this purpose, a home energy management algorithm was developed and simulated in the MATLAB Simulink environment by taking an apartment in Esenler, Istanbul as a reference. The smart home model discussed in this simulation study can generate its own electricity with renewable energy sources, store excess electrical energy in battery groups and also sell the surplus to the grid. This home model also enables end-users to control peak loads and schedule home appliances, especially during peak hours, following a demand-response program to consume energy more efficiently. Then, in order to see the electricity consumption results, electricity bill calculations were made according to both single and triple tariff pricing. The benefits of this model to the consumer and the grid were investigated, and also its effects on efficiency were examined. The results are given comparatively and the consumer’s saving is depicted in figures.